2005
DOI: 10.1007/s10620-005-2771-x
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Toxin A Induces Intestinal Epithelial Cell Apoptosis and Damage: Role of Gln and Ala-Gln in Toxin A Effects

Abstract: The aim of this study was to investigate the effect of Clostridium difficile toxin A (TxA) on intestinal epithelial cell migration, apoptosis, and transepithelial resistance and to evaluate the effect of glutamine (Gln) and its stable derivative, alanyl-glutamine (Ala-Gln), on TxA-induced damage. Migration was measured in rat intestinal epithelial cells (IEC-6) 6 and 24 hr after a razor scrape of the cell monolayer. Cell proliferation was indirectly measured utilizing the tetrazolium salt WST-1. The cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 38 publications
(39 reference statements)
5
47
0
2
Order By: Relevance
“…The GTD has been shown to target and inactivate a number of Rho-family GTPases (19,20). This inactivation has been linked to a cell rounding or cytopathic effect (CPE) (21)(22)(23)(24) and to an apoptotic cytotoxic effect (25)(26)(27)(28)(29)(30)(31)(32)(33). In tissue culture models, the apoptotic effects of TcdA and TcdB occur at toxin concentrations of picomolar or lower and are evident at 24 to 48 h postintoxication (26,28,29,(34)(35)(36).…”
mentioning
confidence: 99%
“…The GTD has been shown to target and inactivate a number of Rho-family GTPases (19,20). This inactivation has been linked to a cell rounding or cytopathic effect (CPE) (21)(22)(23)(24) and to an apoptotic cytotoxic effect (25)(26)(27)(28)(29)(30)(31)(32)(33). In tissue culture models, the apoptotic effects of TcdA and TcdB occur at toxin concentrations of picomolar or lower and are evident at 24 to 48 h postintoxication (26,28,29,(34)(35)(36).…”
mentioning
confidence: 99%
“…Conventionally, cell susceptibility to bacterial toxins and neutralizing antibody responses in vitro rely on radioactive cytotoxicity measurements for protein synthesis or are evaluated by microscopic observations of intoxicated cell monolayers. These methods may be subjective, time-consuming, and inherently low throughput, due to the requirements of manual observation and counting of cells (5,7,9,(19)(20)(21)(22). Because of these limitations, we sought to develop an alternative assay that may be used as a versatile platform for measuring bacterial toxin activity and to evaluate the immunogenicities of toxin-based vaccines.…”
mentioning
confidence: 99%
“…Although a trend toward reduction of apoptosis was seen, we could not show a significant glutamine effect in our in vitro model. Other studies, including our own [46,47], have found a protective role of glutamine in preventing cell apoptosis seen with toxins, atrophy or cytokines [47][48][49] in other more differentiated intestinal cell lines. However, we postulate that apoptosis at the level of undifferentiated stem cells is critical to the effects of 5-FU in preventing the emergence of mutant cell lines in the crypts, which would prevent further neoplasic growth.…”
Section: Discussionmentioning
confidence: 51%
“…The optimal dose of 10 mM of glutamine and alanyl-glutamine show enhanced crypt cell proliferation following 5-FU challenge. The same concentration proved to be beneficial in our previous studies [47,51] with Clostridium difficile toxin A-induced epithelial injury. This concentration used in the medium far exceeds the physiological serum concentration, confirming the high requirement for these peptides for cell growth and adaptation following severe epithelial injury.…”
Section: Discussionmentioning
confidence: 68%